Intra-Abdominal Hypertension and Abdominal Compartment Syndrome. Literature Review - Sh. V. Timerbulatov; U. M. Abdullin; V. V. Viktorov; V. V. Plechev; A. R. Gafarova (Креативная хирургия и онкология, 2024)
Intra-abdominal hypertension and abdominal compartment syndrome remain a challenging problem in abdominal surgery. Due to various etiological factors leading to increased intra-abdominal pressure (inflammatory, destructive processes, trauma, sepsis, postoperative complications, etc.), and the negative impact of increased IBP on the functions of the gastrointestinal, respiratory, cardiovascular systems, kidneys, central nervous system, timely diagnosis and treatment play an important role. Gradually elevated intra-abdominal pressure can cause persistent organ dysfunction and be potentially fatal. To date, the pathophysiological mechanisms, methods for determining intra-abdominal pressure, the frequency of its measurement, and methods of conservative and surgical treatment have been studied in sufficient detail. The paper presents a literature review on the problem of intra-abdominal hypertension and abdominal compartment syndrome. The study considers issues of epidemiology, mortality rates, methods for measuring intra-abdominal pressure, including advanced innovative technologies. The authors present the basics of clinical diagnosis, the significance and informativity of additional biochemical blood tests, radiation methods, mainly computed tomography, and ultrasound examination. Advanced methods of conservative treatment are considered, which, when used early, significantly minimize target organ damage, organ dysfunction, and indications for emergency decompressive laparotomy. Finally, recommendations are given for the postoperative management of patients with an “open” abdomen, and for the optimal timing of laparostoma closure.